Collusion in the football labor market - the effects of misallocations - Ferreira, Luís Maria Mendes de Almeida Cavaleiro de (2022)
This research investigates the existence of structural misallocations of players in the football labor market, in the context of an intervention by the Portuguese Competition Authority against a no-hiring agreement between clubs. We undertook an econometric analysis of two player datasets, from the Portuguese league and from other European leagues. Our main finding is that big teams use more valuable players less, indicating that big teams hoard valuable players. Finally, we conclude that, due to insufficient regulation in each league, structural misallocations contribute to a lack of competitive balance.